ATM‐mediated phosphorylation of SOG1 is essential for the DNA damage response in Arabidopsis. (2nd August 2013) - Yoshiyama, Kaoru O; Kobayashi, Junya; Ogita, Nobuo; Ueda, Minako; Kimura, Seisuke; Maki, Hisaji; Umeda, Masaaki
Abstract : Arabidopsis SOG1 (suppressor of gamma response 1) is a plant‐specific transcription factor that governs the DNA damage response. Here we report that SOG1 is phosphorylated in response to DNA damage, and that this phosphorylation is mediated by the sensor kinase ataxia telangiectasia mutated (ATM). We show that SOG1 phosphorylation is crucial for the response to DNA damage, including transcriptional induction of downstream genes, transient arrest of cell division and programmed cell death. Although the amino‐acid sequences of SOG1 and the mammalian tumour suppressor p53 show no similarity, this study demonstrates that ATM‐mediated phosphorylation of a transcription factor has a pivotal role in the DNA damage response in both plants and mammals. ATM‐mediated phosphorylation of SOG1 is essential for the DNA damage response in Arabidopsis : In plants, SOG1 regulates transcription, cell cycle arrest and cell death in response to DNA damage. This study reports that ATM‐mediated phosphorylation of SOG1 is essential for this response. As SOG1 and p53 have no sequence similarity, they are likely an example of convergent evolution.